Serum Tumour Markers in Testicular Germ Cell Tumours: Frequencies of Elevated Levels and Extents of Marker Elevation Are Significantly Associated with Clinical Parameters and with Response to Treatment. (28th May 2019) - Dieckmann, Klaus-Peter; Simonsen-Richter, Hanna; Kulejewski, Magdalena; Anheuser, Petra; Zecha, Henrik; Isbarn, Hendrik; Pichlmeier, Uwe
Abstract : Introduction . Although serum tumor markers beta human chorionic gonadotropin (bHCG), alpha-fetoprotein (AFP), and lactate dehydrogenase (LDH) are well-established tools for the management of testicular germ cell tumours (GCTs), there are only few data from contemporary cohorts of primary GCT patients regarding these biomarkers. Our aim was to evaluate marker elevations in testicular GCTs and to document their associations with various clinical characteristics. Patients and Methods . A total of 422 consecutive patients with GCTs were retrospectively analysed regarding serum levels of bHCG, AFP, and LDH during the course of treatment. Additionally, the following characteristics were recorded: histology, age, laterality, clinical stage (CS), pT-stage, and tumour size. Marker elevations were first tabulated in dichotomized way (elevated: yes/no) in various subgroups and second as continuous measured serum values. Descriptive statistical methods were employed to look for differences among subgroups and for associations of elevations with clinical parameters. Results . In all GCT patients, the frequencies of elevated levels of bHCG, AFP, LDH, and bHCG or AFP were 37.9%, 25.6%, 32.9%, and 47.6%; in pure seminomas 28%, 2.8%, 29.1%, and 30.3%; and in nonseminoma 53.0%, 60.1%, 38.7%, and 73.8%. Significant associations were noted with pT-stages >pT1, clinical stages >CS1, tumour size, and younger age. Frequencies of marker elevations dropped significantly after treatment, but LDH levels remained elevated in 30.5%-34.1%. Relapsing patients (n=27) had elevated levels of bHCG, AFP, and LDH in 25.9%, 22.2%, and 29.6%, respectively, thirteen of whom with a changed marker pattern. Conclusions . The classical GCT-biomarkers correlate with treatment success. Clinical utility is limited due to proportions of < 50% of patients with elevated levels and the low specificity of LDH. The elevation rates are significantly associated with histology, clinical and pT-stages, tumour size, and younger age. Individual marker patterns may change upon relapse. Clinically, ideal biomarkers are yet to be found.